A Review of Face Spoof Detection Techniques - Nikhil Singh,; Sandeep Singh, (Journal of Electronic Design Engineering, 2021)
In many applications such as crossings, banks, and mobile payments, face recognition systems are now being utilized. An intensive focus on the reliability of facial biometrics against a spoof attack was the extensive deployment of facial recognition systems where a photo, video, or 3D mask with genuine visual users can be used for unlawfully accessing facilities or services. Although several facial anti-spoofing methods or animal life detection methods were suggested that determine whether a face is spoofed or alive, the problem remains unsolved because of the difficulty in finding discriminatory and computer-cheap characteristics and techniques for spoof attacks. Existing techniques also use full-face images or full video for detection of liveliness. However, some facial regions are often redundant or match the image's clutter, leading to low performance in general. In this paper, a comprehensive review of various face spoof detection has been presented.